Validation of the healthcare workers’ version of the Pandemic Grief Scale among frontline nursing professionals during the COVID-19 pandemic in Korea - Kim, Jeong Hye; Park, C. Hyung Keun; Ahmed, Oli; Hong, Youjin; Chung, Seockhoon; Park, Jangho; Lee, Sherman A. (Frontiers in Psychiatry, 2023)
Introduction: Nurses have been repeatedly exposed to unexpected death and grief during COVID-19 pandemic, and it is necessary to provide grief support for the nurses who have experienced the loss of patients to COVID-19. We aimed to explore the reliability and validity of the Pandemic Grief Scale (PGS) for Healthcare Workers among frontline nursing professionals working in COVID-19 inpatient wards whose patients may have died. Methods: An anonymous online survey was performed among frontline nursing professionals working in COVID-19 wards in three tertiary-level general hospitals in Korea between April 7 and 26, 2021. Among 266 responses, 229 from participants who confirmed they had witnessed death of patients were employed for the statistical analysis. The survey included demographic characteristics and rating scales, including the Korean version of the PGS for Healthcare Workers, the Fear of COVID-19 scale, the Generalized Anxiety Disorder-7 items, and the Patient Health Questionnaire-9 items. Results: The single-factor structure of the Korean version of the PGS for Healthcare Workers showed good fits for the model. The scale had good internal consistency and convergent validity with other anxiety and depression scales. Conclusion: The Korean version of the PGS of Healthcare Workers was valid and reliable for measuring grief reactions among nursing professionals facing the pandemic. It will be helpful in evaluating the grief reaction of the healthcare workers and providing them with a psychological support system.